Diagnosis and seismic behavior evaluation of the church of São Miguel de Refojos (Portugal) - Ramírez, Rafael (2019)
The Benedictine Monastery of São Miguel de Refojos, located in Cabeceiras de Basto (Portugal), is a monumental complex and a distinctive example of the 18th century Portuguese Baroque architecture. This study addresses the state of conservation of the church as well as the evaluation of its structural behavior and seismic performance. An initial inspection and diagnosis campaign revealed that the structure presents low to moderate damage and other non-structural issues generally associated with high levels of moisture and water infiltration. In order to study the structural performance, a three-dimensional (3D) numerical model was prepared based on the finite element method. This model was calibrated with respect to dynamic identification tests and nonlinear static analyses were then performed to evaluate the seismic behavior. Capacity curves, deformations, crack patterns, and failure mechanisms were used to characterize the structural response. Additionally, the safety evaluation for horizontal actions was verified by means of limit analysis. An overall good agreement was found between the results of the pushover and the limit analyses. To conclude, the present work provides a comprehensive evaluation of the state of conservation of the church and verifies the safety condition of the structure for seismic actions.